2004
DOI: 10.1002/jemt.20131
|View full text |Cite
|
Sign up to set email alerts
|

New approach to quantifying developmental variation in the dentition using serial microtomographic imaging

Abstract: KEY WORDSserial microtomographic imaging; tooth development; deciduous molar ABSTRACT Dental morphogenesis and cellular differentiation are expressed in the fully formed tooth by the topography of the dentin-enamel junction and outer enamel surface. These boundaries can be differentiated using a variety of imaging systems. In this study, we used serial microCT imaging to provide accurate 3D reconstructions of developing lower human second deciduous molars. These were used to quantify the volume of enamel and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This interface represents the initial position of the cells that are responsible for enamel and dentine secretion and is believed to be heavily influenced by embryological enamel knots that form before hard-tissue secretion (reviewed in Avishai and colleagues 93 and Skinner and colleagues 94 ). Olejniczak and colleagues, 85,[95][96][97] have demonstrated that the primate EDJ has a taxon-specific shape, despite some intra-taxon variation, and that components of this shape, such as relative dentine horn height, may serve to group members of the Ponginae.…”
Section: Enamel-dentine Junction Shapementioning
confidence: 98%
“…This interface represents the initial position of the cells that are responsible for enamel and dentine secretion and is believed to be heavily influenced by embryological enamel knots that form before hard-tissue secretion (reviewed in Avishai and colleagues 93 and Skinner and colleagues 94 ). Olejniczak and colleagues, 85,[95][96][97] have demonstrated that the primate EDJ has a taxon-specific shape, despite some intra-taxon variation, and that components of this shape, such as relative dentine horn height, may serve to group members of the Ponginae.…”
Section: Enamel-dentine Junction Shapementioning
confidence: 98%
“…A number of studies have examined the repeatability of measurements (and inter-and intraindividual errors in locating landmarks) from mCT images of trabecular bone (e.g., Durand and Rü egsegger, 1991;Balto et al, 2000), tooth root canals (Peters et al, 2000), and tooth enamel (Avishai et al, 2004). To date, however, the only studies that have attempted to assess the accuracy of measurements derived from high-resolution X-ray computed tomography have been conducted with reference to trabecular bone configuration (Kuhn et al, 1990;Mü ller et al, 1996aMü ller et al, ,b, 1998Hildebrand et al, 1999;Fajardo et al, 2002), periapical and periradicular alveolar bone destruction (Balto et al, 2000;von Stechow et al, 2003), the diameters of tooth root canals (Rhodes et al, 1999), and cortical bone porosity (Cooper et al, 2004).…”
mentioning
confidence: 99%
“…McErlain et al (2004) examined a single tooth from a 420-year-old Late Iron Age site in Cambodia and simply commented that they were clearly able to differentiate visually the hard tissue components, which were displayed with "exceptional clarity." The study by Avishai et al (2004) examined individual error rates in locating landmarks (and resultant measurements) in a series of tooth germs derived from archeological contexts.…”
mentioning
confidence: 99%
“…Rat incisors were studied by Wong et al with a special emphasis on the dentin-enamel junction [20]. Developing human molars were studied by Avishai et al [21]. We have studied the pharyngeal teeth of zebrafish [22].…”
Section: Discussionmentioning
confidence: 98%